2019
DOI: 10.1111/1750-3841.14655
|View full text |Cite
|
Sign up to set email alerts
|

Composition, Antivirulence Activity, and Active Property Distribution of the Fruit of Terminalia chebula Retz

Abstract: The fruit of Terminalia chebula Retz., or Tibet Olive, is widely used as a food supplement in China. It possesses some natural antimicrobial properties; however, its chemical composition and antivirulence effects have not been identified. In this work, 29 compounds were identified from the peel of T. chebula fruit by ultra‐high‐performance liquid chromatography‐tandem quadrupole time‐of‐flight mass spectrometry. Both the extract of T. chebula and its phenolic acid, corilagin, showed antivirulent activity again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Terminalia chebula ( T. chebula ) belongs to the family of Combretaceae and is mostly found in the Asian region [ 283 ]. It is one of the most important medicinal plants due to the presence of a huge number of different kinds of phytoconstituents [ 232 ].…”
Section: Other Medicinal Plants In Use Against Various Viral Infecmentioning
confidence: 99%
See 1 more Smart Citation
“…Terminalia chebula ( T. chebula ) belongs to the family of Combretaceae and is mostly found in the Asian region [ 283 ]. It is one of the most important medicinal plants due to the presence of a huge number of different kinds of phytoconstituents [ 232 ].…”
Section: Other Medicinal Plants In Use Against Various Viral Infecmentioning
confidence: 99%
“…It is one of the most important medicinal plants due to the presence of a huge number of different kinds of phytoconstituents [ 232 ]. It is customarily used as a household remedy and also in modern, Ayurveda, Unani and Homoeopathic medicines [ 232 , 283 ]. Its bioactive components extracted from the leaves, bark and fruit of the plant include flavonoids, polyphenols, terpenes, anthocyanins, glycosides, gallic acid, chebulagic acid, punicalagin, chebulanin, corilagin, neochebulinic acid, ellagic acid, chebulinic acid, alkaloids and many more [ 232 , 237 , 284 ].…”
Section: Other Medicinal Plants In Use Against Various Viral Infecmentioning
confidence: 99%
“…Compound 18 could inhibit biofilm formation, quorum sensing, and toxin secretion. This indicated that corilagin might be an effective antibacterial compound [183]. Compound 11 efficiently blocked entry of HCV of all major genotypes and also of the related flavivirus Zika virus [184].…”
Section: Biological Activitymentioning
confidence: 99%
“…In Chebulae Fructus, gallic acid structure was found in carboxylic acids ( P13 chebulic acid [ 42 ], P23 gallic acid [ 23 , 43 ], P26 5-galloylshikimic acid [ 44 ], P33 brevifolincarboxylic acid [ 45 ], and P40 3,4,8,9,10-pentahydroxydibenzo[b,d]pyran-6-one [ 44 ]), while ellagic acid (gallic acid dimer) structure was tannins ( P28 hamamelitannin [ 46 ], P29 1,6-di-O-galloyl- β -D-glucose [ 47 ], P34 chebulanin(1-O-galloyl-2,4-O-chebuloyl-b-D-Glc [ 44 ]), P36 corilagin [ 48 ], and P41 chebulagic acid [ 46 ]). Thus, ellagic acid fragment ( m/z of 300) and neutral loss of gallic acid (170 Da) could be generally observed.…”
Section: Resultsmentioning
confidence: 99%